Ascorbic Acid, Corticosteroids and Thiamine in Sepsis (ACTS) protocol and statistical analysis plan: a prospective, multicentre, double-blind, randomised, placebo-controlled clinical trial. Issue 12 (17th December 2019) - Moskowitz, Ari; Yankama, Tuyen; Andersen, Lars W; Huang, David T; Donnino, Michael W; Grossestreuer, Anne V
Abstract : Introduction: Septic shock is a common and highly morbid condition. To date, there is no specific therapy proven to attenuate organ injury in septic shock. Recent studies have suggested a role for the combination of ascorbic acid, corticosteroids and thiamine, although randomised data are lacking. Methods and analysis: The Ascorbic Acid, Corticosteroids, and Thiamine in Sepsis trial is a multi-centre, double-blind, randomised, placebo-controlled clinical trial that aims to determine the impact of ascorbic acid, corticosteroids and thiamine versus placebo on organ injury and mortality in patients with septic shock. Patients are randomised to receive 1500 mg of ascorbic acid, 100 mg of thiamine and 50 mg of hydrocortisone parenterally versus matching placebo every 6 hours for 4 days. Clinical and laboratory data are collected at the time of study enrolment, at 24, 72 and 120 hours. The primary end-point for the trial is change in the Sequential Organ Failure Assessment score between enrolment and 72 hours. Additional key secondary outcomes include the incidence of renal failure and 30-day mortality. Ethics and dissemination: The study was approved by the international review board of each participating study site. Study findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: The trial is registered on clinicaltrials.gov (NCT03389555 ). It was posted on 3 January 2018.